Towards a cargo HUB the trinidad and tobago case - Henry, Joseph. (2009)
In trying to determine what are the critical success factors for Trinidad and Tobago to become an air cargo hub, the literature was reviewed to determine how much work was done on this phenomenon in the past. The Singapore success story was chosen as a benchmark for the performance of an air cargo hub as there exist similarities between Singapore and Trinidad and Tobago such as both being island states and they lie between major international trading blocks.